2016
DOI: 10.1002/masy.201500010
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐Optical Properties of Amino Acid Modified ZnO‐PVA Colloidal Suspension Under CW Laser Illumination

Abstract: Summary In this paper, we present synthesis of amino acids (l‐arginine and l‐alanine) assisted surface modification of ZnO nanoparticles (NPs) using chemical precipitation method. Study emphasizes the utility of l‐arginine over l‐alanine in the synthesis process and ZnO NPs with average particle size of 18 nm have been successfully obtained using l‐arginine. Structural properties were evaluated using powder X‐ray diffraction (XRD) pattern, energy dispersive X‐ray spectroscopy (EDAX) and transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The peak at 440 cm −1 could be due to the stretching vibrations of ZnO. 23 The hydroxyl groups on the surface of the ZnO NRs resulted from its hygroscopic nature. 23 Collectively, these observations suggested that the FTIR-identified impurities primarily existed near the ZnO surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak at 440 cm −1 could be due to the stretching vibrations of ZnO. 23 The hydroxyl groups on the surface of the ZnO NRs resulted from its hygroscopic nature. 23 Collectively, these observations suggested that the FTIR-identified impurities primarily existed near the ZnO surface.…”
Section: Resultsmentioning
confidence: 99%
“… 23 The hydroxyl groups on the surface of the ZnO NRs resulted from its hygroscopic nature. 23 Collectively, these observations suggested that the FTIR-identified impurities primarily existed near the ZnO surface. In case of ZnO– l -Alanine, the FTIR spectrum showed a peak at 3398 cm −1 due to the O–H stretching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation